Komunikasi dan Advokasi Kebijakan Terhadap Manajemen Publik Melalui Lembaga Swadaya Masyarakat Kota Medan - Lubis, Khairunnisah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to determine communication and policy advocacy towards public management through non-governmental organizations in the city of Medan. This research method uses library research by collecting relevant studies from books, literature, notes and reports. The results of this study indicate that the Pesada NGO has succeeded in implementing all elements of advocacy in non-profit organizations, judging from the success of the programs carried out by the Pesada institution.